Monitoring wellbeing and perceived exertion in relation to injury risk in elite female football players over 2 seasons - Larruskain, J.; Uria, A.; Aldalur, M.; Iturregi, I.; Yarritu, A.; Bikandi, E.; Arce, J.; Monasterio, X.; Lekue, J. A.; Martin-Garetxana, I. (British Journal of Sports Medicine, 2021)
Background There is a gap in understanding how to use wellbeing and load measures in football, particularly in women.